Recent studies on knowledge, attitude, and practice toward tuberculosis among university students - Lutfiah Yusuf, Irma Melyani Puspitasari, Rano Kurnia Sinuraya, (Journal of Applied Pharmaceutical Science, 2021)
According to the World Health Organization, tuberculosis (TB) remains the most dangerous infectious disease, causing a major problem for public health globally. Lack of knowledge and negative attitudes toward TB create immense challenges in the prevention, controlling, and curing of TB disease. Students have a high risk of contracting TB. This article summarizes the knowledge, attitudes, and practices regarding TB among university students, using a literature search conducted through a PubMed electronic database in March 2020 that yielded 12 articles from a total of 64. The studies were conducted worldwide, with 5,915 university student participants. This study revealed that students in 8 out of 12 studies had poor knowledge levels, students in two of six studies had a negative attitude, and 11.6% of the students in a study had poor practices toward TB. Curriculum innovation regarding infectious diseases is needed to improve TB knowledge, attitudes, and practice among students.
Keywords: Tuberculosis, knowledge, attitude, practice, university student